Holocene coral reef growth and sea level in a macrotidal, high turbidity setting: Cockatoo Island, Kimberley Bioregion, northwest Australia - Solihuddin, T.; Collins, Lindsay; Blakeway, D.; O'Leary, M. (Elsevier Science BV, 2015)
The inshore Kimberley Bioregion of northwest Australia is a macrotidal, low wave energy, frequent cyclones, and high turbidity setting with abundant fringing coral reefs. Here we describe the Holocene development of a sheltered fringing reef at Cockatoo Island in the Kimberley, using data from reef cross-sections subaerially exposed in an iron ore mining pit, seismic profiles across the adjacent contemporary reef, and GIS and ground truth mapping of contemporary reef habitats. Subsidence since the Last Interglacial has provided accommodation for ~13–20m of Holocene reef accretion upon an older, probably Last Interglacial, reef. In the pit cross-sections, the reef initiated at ~9000 cal y BP and accreted in a catch-up mode, reaching sea level at ~3000 cal y BP, and reef accretion rates varied from26.8mm/year to 0.8mm/year, averaging ~2mm/year. The catch-up interpretation is supported by the predominance of branching Acropora throughout the Holocene section and the absence of contemporary intertidal indicators such as Porites cylindrica and Millepora intricata. This pattern differs from the otherwise similar mud-rich but mostly microtidal inshore fringing reefs of the Great Barrier Reef, which initiated in the late Holocene on shallow substrates under a stable sea level. The study provides the first Holocene reef growth history for an inshore Kimberley reef within a biodiversity “hotspot”.